Pelatihan Pembuatan Bahan Ajar Dan Instrumen Evaluasi Menggunakan Aplikasi Microsoft Kaizala - Nenden Mutiara Sari; Poppy Yaniawati; Eka Firmansyah; In In Supianti; Melinda Putri Mubarika (Ilin Institute, 2021)
The purpose of holding Microsoft Kaizala training is to train teachers' skills in making teaching materials according to the stages of problem solving exploration. This community service activity was attended by 163 participants, with the target activities being mathematics teachers and mathematics education students. The methods of implementing the service carried out are: (1) surveying the effectiveness of online mathematics learning; (2) forum group discussion (FGD); (3) webinars on the use of the microsoft kaizala application; (4) assistance in making teaching materials and evaluation instruments with the Microsoft Kaizala application and (5) evaluating the implementation of community service. The results of the evaluation showed that in general the participants expressed satisfaction with the implementation of community service activities that had been carried out.